Inclusion Complexes of Hydroxy Propyl-β-Cyclodextrin and Paliperidone: Preparation and Characterization - Sherje, Atul; Londhe, Vaishali (Current Drug Discovery Technologies, 2014)
In the present investigation, an attempt has been made to improve aqueous solubility of a BCS class II drug by making an inclusion complex with Hydroxypropyl-β-cyclodextrin (HP-β-CD). Paliperidone (PALI) was selected as a model drug for the study. It is practically insoluble in water with low oral bioavailability. It is a major active metabolite of risperidone approved for the treatment of schizophrenia in adults. The inclusion complexes were prepared in 1:1 (PALI: HP-β-CD) molar ratio. Phase solubility studies were performed according to Higuchi Connors method to determine the optimum conditions for the complexation. The prepared solid inclusion complexes were characterized by Differential Scanning Calorimetry (DSC), Fourier- Transform Infrared Spectroscopy (FT-IR), Powder X-ray Diffractometry (PXRD), Scanning Electron Microscopy (SEM) and Proton Nuclear Magnetic Resonance Spectroscopy (1H-NMR). Dissolution study was performed using USP apparatus II in phosphate buffer, pH 6.8 (37 ± 0.5°C). The solid state characterization studies confirmed the formation of inclusion complex between PALI and HP-β-CD. The aqueous solubility and in-vitro dissolution study showed that the solubility and dissolution rate of drug were considerably improved by complexation with HP-β-CD with respect to the drug alone. The enhanced solubility and dissolution may help to improve in-vivo performance of PALI. Thus, the binary complexation of PALI with HP-β-CD can be used as an approach for its solubility enhancement.
Keywords: poorly soluble